Resiliensi Akademik Mahasiswa Terhadap Pandemi Covid – 19 - Della, Andi (Indonesian Journal of Islamic Counseling, 2021)
Resilience or Toughness is very important, especially for students to be able to survive and be able to overcome problems that occur during the world pandemic which is being hit bye The Covid 19 pendemic,making people very limited in carrying out daily activities. Students to carry out virtual online learning activities. Various sectors, especially the education sector, which require students to carryout virtual online learning activities students with various assignments given by lecturers are required to be able to survive in today difficult conditions. The strategic is to build positive emotions and spiritualismand solve problems rationally and be able to get out of troble . the academic problems he faced. What was done during the pandemic to build student resilience, namely the strategic application carried out by prophet yusuf, the results of the research showed that individual factors in building resilience, especially the individual independence factor or social support.